2000
DOI: 10.1002/1097-4628(20001114)78:7<1341::aid-app40>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of chemically modified gelatin films in soil

Abstract: Gelatin films that had been chemically modified (crosslinked with formaldehyde, glyoxal, glutaraldehyde, hexamethylene diisocyanate, butadiene diepoxide, or diepoxyoctane) were tested for their biodegradability by soil burial testing in a laboratory environment under temperature and humidity control. The relationship between weight loss and time of biodegradation showed a linear behavior for all the samples, but the rate of biodegradation showed a dependence on the type of crosslinking agent. The most stable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…The results obtained were very similar to those observed in the case of river and lake water exposure 3. It was shown that the rate of biodegradation depended on the network density of the samples 5…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results obtained were very similar to those observed in the case of river and lake water exposure 3. It was shown that the rate of biodegradation depended on the network density of the samples 5…”
Section: Introductionsupporting
confidence: 85%
“…The same samples were tested for their biodegradability by burial testing under laboratory conditions with controlled temperature and humidity 5. The results obtained were very similar to those observed in the case of river and lake water exposure 3.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is well known that gelatin‐based materials are susceptible to the action of enzymes (proteases) which are present in a variety of microorganisms 1, 44. Gelatin is also sensitive to the attack of filamentous fungi under humid conditions 45, 46.…”
Section: Resultsmentioning
confidence: 99%
“…This result was mainly attributed to the biocide activity of phenol from phenolic resin. The biodegradation of chemically modified gelatin films was also analyzed in different environments such as river and lake water and in soil under laboratory conditions 1, 44. It was shown that the rate and extent of biodegradation depended on the type of crosslinking reagent and on the crosslinking density.…”
Section: Resultsmentioning
confidence: 99%